Adoption Computerized Certificate Transparency And Confidentiality - Deden Rustiana; Julysar Diti Pratama; Taufan Mudabbir; Muhamad Ali Fahmi; Galih Ahmad Rofei (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2022)
Due to the unavailability of issuing entities, the increasing number of valuable documents that are still being issued in printed form has an impact on forgery and cannot be verified. Academic certification is an achievement that everyone desires because it has a positive effect and has a continuity in their social life. These activities are listed as being able to identify, analyze, and try out any of the ledger options that are available. arise to provide greater efficiency, reliability, and a level of independence. By implementing a prototype that could issue, verify, and distribute certificates, the fact of the concept was proposed. The experimental test results are given, as well as the use of blockchain technology for the purpose of analyzing. Finally, this work outlines the current growth and maturity of equipment encountered, reports progress and limitations, and reveals issues that still need to be addressed.